Iran v 'the international community': a postcolonial analysis of the negotiations on the Iranian nuclear program*. Issue 3 (2nd September 2018) - Biswas, Shampa
ABSTRACT: This paper undertakes an analysis of the underlying presuppositions and terms of the international negotiations on the Iranian nuclear programme as covered in the mainstream Western media during 2013–14. Examining the deep-seated Orientalist presuppositions underlying the civilizational narrative through which the rivalry between the US/West and Iran is described, the paper argues that the notions of 'nuclear responsibility', 'international community', and 'global peace' generated by such representations obscure global power and hierarchy. In effect, such a discourse ensures that Iran remains caught in the spotlight of dangerous nuclear transgressions while the nuclear programme of a normative West is rendered unremarkable.